1994
DOI: 10.1063/1.111169
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of semiconductor doping by scanning resistance microscopy

Abstract: Coupling scanning tunneling microscope and supersonic molecular beams: A unique tool for in situ investigation of the morphology of activated systems Rev. Sci. Instrum. 83, 093703 (2012) Inelastic tunneling spectroscopy of gold-thiol and gold-thiolate interfaces in molecular junctions: The role of hydrogen J. Chem. Phys. 137, 094703 (2012) Scanning tunneling microscopy/spectroscopy studies of resistive switching in Nb-doped SrTiO3 J. Appl. Phys. 112, 023703 (2012) Two-step controllable electrochemical etchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…Our numerical calculations showed that the existence of inhomogeneous doping can strongly modify the electronic properties of doped quantum wells, being at least as important as nonabrupt interface effects. Despite limitations on the knowledge of Si diffusion in GaAs and Al x Ga 1−x As [16], and the limited spatial resolution (∼30 nm) achieved nowadays by the experimental methods used to probe dopant profiles [4][5][6][7], we believe that future experiments on inhomogeneous doping characterization and on the electron intersubband transitions in inhomogeneous doped single nonabrupt GaAs/Al x Ga 1−x As quantum wells will validate the assumptions of our inhomogeneous doping model and confirm our main results.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Our numerical calculations showed that the existence of inhomogeneous doping can strongly modify the electronic properties of doped quantum wells, being at least as important as nonabrupt interface effects. Despite limitations on the knowledge of Si diffusion in GaAs and Al x Ga 1−x As [16], and the limited spatial resolution (∼30 nm) achieved nowadays by the experimental methods used to probe dopant profiles [4][5][6][7], we believe that future experiments on inhomogeneous doping characterization and on the electron intersubband transitions in inhomogeneous doped single nonabrupt GaAs/Al x Ga 1−x As quantum wells will validate the assumptions of our inhomogeneous doping model and confirm our main results.…”
Section: Resultssupporting
confidence: 66%
“…Following indications of experimental results concerning inhomogeneous doping patterns [4][5][6][7], we described the inhomogeneous Si-doping concentration profile N D (z) in the growth direction z by the following expression:…”
Section: The Inhomogeneous Doping Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…SPM techniques [1] have been widely used to characterize semiconductors at room temperature: capacitance [2][3][4] and resistance [5] profiling of carrier distributions have been demonstrated, and trapped charge has been deposited and observed via both force [6] and capacitance [7] microscopy. Recently we have demonstrated the use of an atomic force microscope with a conducting tip at 4.2 K to characterize ballistic electron flow through a point contact in a two-dimensional electron gas (2DEG) located beneath the surface of a GaAs/AlGaAs heterostructure [8].…”
Section: Introductionmentioning
confidence: 99%